Karakterisasi dan Analisis Gerombol Plasma Nutfah Jarak Pagar Indonesia dan Beberapa Negara Lain Menggunakan Marka Morfologi dan Molekuler - Memen Surahman; Edi Santosa; Fifin Nashirotun Nisya (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
Characterization is important in breeding program and developing superior varieties of jatropha.  Jatropha characterization can be analyzed based on its morphological and agronomical characteristics.  In this study, a molecular marker, Random Amplified Polymorphic DNA (RAPD), was applied for cluster analysis.  This study was aimed at analyzing character and similarity of 30 jatropha germplasms of SBRC-IPB collection. Results showed that 30 jatropha accessions have high character variability.  Dendogram of RAPD marker showed that at 33% similarity level, the 30 jatropha accessions could be classified into three main groups.  It was also shown that Papua and China accessions had similarity levels higher than 80%.  Based on production characteristic identification, the potential accessions to be developed further included Palembang, Pontianak, Pidi, Palembang I, Pagar Alam, Medan, Curup, Lampung I, Lampung II, Komering, and Indralaya.   Key words:  Jatropha curcas L., characterization, cluster analysis, morphological marker, RAPD marker